Reviewed book: Ona RAKAUSKIENE, Dalia STREIMIKIENE, Lina VOLODZKIENE (2025), Strengthening Human and Societal Resilience in Uncertain Times, Routledge, 352 p. - Streimikis, Justas (Transformations In Business & Economics, 2025)
Reviewed book: Ona RAKAUSKIENE, Dalia STREIMIKIENE, Lina VOLODZKIENE (2025), Strengthening Human and Societal Resilience in Uncertain Times, Routledge, 352 p.
Keywords: Y30